Наугад: стихи всяких лет / Р.Ф. Казакова - Казакова Римма Федоровна (Academia, 1995)
Экземпляры: ФИЛ (19971129) / Инвентарный номер: 1021680 / Цена: 5000.00 / Сис.шифр: Р2 / Авт.знак: К 14 / ГРНТИ: 17 / ББК: 84(2)